Maintaining Progresiveness of Personal Income Tax Rates in The Indonesian Income Tax Law - Suwardi Suwardi (Pertapsi-Indonesia collaborated with Petra Christian University, 2023)
This research is related to the argumentation of the plans of several tax authorities, including the Indonesian authorities, to increase the personal income tax rate. The imposition of taxes through increased individual tax rates is one way for post-Covid-19 funding. The increase in tax rates is considered not to pose a risk to consumption or the principle of tax equity. This study uses a descriptive quantitative research method that tries to explain the planned increase in tax rates by the Indonesian tax authorities is by international trends or practices, the principle of justice, and taxpayer behavior. The comparison of the taxable lower limit, rate, GDP Per Capita, PKP Upper Limit, Number of Taxable Layers, and the impact of changes in individual tax rates are used to explain this research. The G-20 and ASEAN countries were selected based on the GDP per Capita scheme and geographical proximity. This study aims to answer the relevance of the implication of imposing progressive rates with Indonesian conditions, the plan to increase tax rates for Personal Income Tax and increase the number of taxable layers. The review of the threshold of taxable income also gets a portion of this research as well. This study also reviewed the rate mantaing from 30% to return to the 35% rate. The results of the study show that the wishes of the Indonesian tax authorities are in line with trends in state financing after the Covid-19 pandemic. This rate increase is not without risk. This rate increase will have implications for changes in the behavior of individual taxpayers who are affected by regulatory changes. The plan to change the individual tax structure should also consider the principles of fairness, progressiveness, general principles of tax reform, and changes in the behavior of taxpayers who are affected by regulatory changes. Changes in tax rates should increase taxpayer voluntary compliance.